2012
DOI: 10.1016/j.susc.2012.07.024
|View full text |Cite
|
Sign up to set email alerts
|

Equilibrium faceting formation in vicinal Al2O3 (0001) surface caused by annealing

Abstract: We report on a heat-induced transformation of the surface of α-alumina (0001) crystals which have a off-cut in the [1210] direction. Annealing the crystal causes the surface to transform into a regular array of (0001) and (1216) facets. The resultant faceted morphology represents the equilibrium state of the system. It is demonstrated that the average terrace periodicity is determined by the annealing temperature. Possible causes for the surface rearrangement are also discussed. The method could be used for pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 26 publications
2
18
1
Order By: Relevance
“…• C in atmosphere for 16 h. 37,38 AFM analysis confirmed the texturing of the template with a measured periodicity L y = 130 nm. The sample was then loaded in a ultrahigh vacuum chamber (base pressure 2 × 10 −8 mbar) and Ag was deposited at a glancing angle of 6…”
Section: Experimental Methodsmentioning
confidence: 60%
“…• C in atmosphere for 16 h. 37,38 AFM analysis confirmed the texturing of the template with a measured periodicity L y = 130 nm. The sample was then loaded in a ultrahigh vacuum chamber (base pressure 2 × 10 −8 mbar) and Ag was deposited at a glancing angle of 6…”
Section: Experimental Methodsmentioning
confidence: 60%
“…(0001) Al 2 O 3 surface morphology is well known to strongly depend on preparation procedure e.g. cleaning methods, annealing time [23,24] and temperature [23][24][25][26], and atmosphere [27] Pt film structure and its surface roughness are also extremely sensitive to heat treatment and even small deviations from specific temperature may result in different growth mode. As it was reported before [18][19][20] by manipulating the substrate temperature during deposition or post-annealing time and temperature one may engineer Pt films of different structure.…”
Section: Substrate Preparation and Sample Growthmentioning
confidence: 99%
“…[29][30][31] The surface morphology of the SrTiO 3 vicinal substrates was examined with an Asylum Research MFP-3D AFM. To produce uniform and straight steps, the SrTiO 3 vicinal substrates were chemically cleaned and then annealed in air in a high temperature furnace at 1130°C for 3 hours.…”
Section: Sample Preparation and Characterizationmentioning
confidence: 99%
“…26 As RS in Fe 3 O 4 can only be observed below the Verwey transition temperature and the switching field is 2 orders of magnitude lower than that for the Zener breakdown (10 6 V cm −1 ), it is believed that RS in Fe 3 O 4 is related to spin-charge ordering or the strongly correlated effect and it is explained by an effect analogous to an electrical-field-driven metal-insulator transition. See DOI: 10 29 may offer an interesting platform to do this. A recent experiment has shown that an electrical field can slightly shift the Verwey temperature T v but does not disrupt the Verwey transition itself.…”
mentioning
confidence: 99%